The proteostatic effects of traffic-derived air pollution on Alzheimer's disease risk - Kikis, Elise A. (Open Biol, 2020)
Alzheimer's disease (AD) is an age-related neurodegenerative disease and the leading cause of dementia in the elderly. Recent decades have been marked by considerable advances in our understanding of genetic and environmental risk factors and also of the AD mechanism(s) of action. Nonetheless, there is still no cure and the myriad ways AD affects the brain is overwhelmingly complex. Such complexity is manifest in part by the fact that genetic background interacts with the environment, including traffic-derived particulate air pollution, to greatly exacerbate AD risk. Determining the mechanisms by which particulate air pollution acts as an AD risk factor has the potential to reveal yet unknown aspects of AD pathology. This review carefully peels back the layers of complexity to discern whether a unifying disease model, one with proteostasis imbalance at its core, holds up to scrutiny in light of the recent literature. While the data are compelling, it is now time for carefully designed studies to definitively determine whether particulate air pollution acts with ageing, genetic background and other sources of proteotoxic stress to disrupt the delicate proteostasis balance.